Dampak Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening (Studi Pada Perusahaan LQ45 yang Terdaftar Di BEI Periode 2016-2020) - Victor Pattiasina; Entar Sutisman; Dwi Septa Rini; Sumartono Sumartono (Jurnal Pasar Modal dan Bisnis, 2022)
This review was coordinated to check out the effect of corporate social commitment on firm worth with usefulness as a mediating variable on LQ45 shares recorded on the Indonesian stock exchange for the 2016-2020 period. The quantity of occupants in this survey is the LQ45 stock document recorded on the Indonesian stock exchange for the 2016-2020 period, which is 45 associations. Considering the purposive investigating methodology, an illustration of 21 associations was gotten. This audit uses the methodology for documentation obtained from financial rundowns circulated on the site www.idx.co.id. The assessment system used is diverse straight backslide. The eventual outcomes of the survey show that: 1) corporate social commitment (CSR) generally influences the usefulness of the LQ45 stock record recorded on the Indonesian stock exchange for the 2016-2020 period. 2) efficiency tremendously affects association regard on the LQ45 stock rundown recorded on the Indonesian stock exchange for the 2016-2020 period. 3) corporate social commitment (CSR) no affects the value of the association in the LQ45 stock record recorded on the Indonesian stock exchange for the 2016-2020 period. 4) efficiency can mediate the effect of corporate social commitment (CSR) on association regard on the LQ45 stock rundown recorded on the Indonesian stock exchange for the 2016-2020 period.